Synthesis of phthalonitrile derivatives by photoinduced reactions: New unsymmetrical substituted zinc phthalocyanines - Tempesti, Tomas Cristian (2015)
The synthesis of new phthalonitrile derivatives by photoinduced reaction is described. Novel unsymmetrically substituted Zn(II) phthalocyanine bearing an aryl alcohol group (ArZnPc) was synthesized by the ring expansion reaction of boron(III) subphthalocyanine chloride with an appropriated phthalonitrile. The spectroscopic and photodynamic properties of these ArZnPc were studied.